Perilaku Konsumen dalam Keberhasilan Le Minerale sebagai Merek AMDK dengan Brand Advocacy Ratio Tertinggi - Ana Rufa Ida; Naili Rifqotun Nadia; Silvy Dewi Anggraini; Nesha Arlinda Revania; Hadisa Amala Lia; Kristinawati Kristinawati; Latifu Nur Rokmah (EKALAYA : Jurnal Ekonomi Akuntansi, 2026)
The success of Le Minerale as the most recommended bottled drinking water (BDW) brand in Indonesia, achieving a Brand Advocacy Ratio (BAR) of 0.62 in the Indonesia WOW Brand 2026 ranking, represents an important consumer behavior phenomenon worthy of further investigation. This study aims to analyze the consumer behavior underlying this achievement from the perspective of consumer behavior theory and to develop a conceptual model explaining the formation of brand advocacy. A qualitative approach was employed using library research combined with document analysis. The primary data were obtained from Marketeers publications, while supporting data were collected from purposively selected national and international scholarly articles. Data were analyzed using content analysis, including coding, categorization, theme identification, data presentation, and source triangulation. The findings indicate that Le Minerale’s high BAR results from the interaction of cultural, social, personal, and psychological factors throughout the consumer decision-making process. This process is further strengthened by the influence of reference groups, family, social media, and electronic word of mouth (e-WOM), which collectively encourage brand advocacy. The study proposes three conceptual propositions regarding the mediating roles of reference groups and family, social media and e-WOM, and brand trust in shaping brand advocacy. The resulting conceptual model provides a theoretical contribution and offers a foundation for future quantitative studies to empirically examine these proposed relationships.